Unintended conceptions leading to wanted pregnancies – an integral perspective on pregnancy acceptance from a mixed-methods study in Germany. (4th May 2021) - Helfferich, Cornelia; Gerstner, Dominik; Knittel, Tilmann; Pflügler, Carina; Schmidt, Franziska
Abstract: Objective: The study examines the differences within unintended first pregnancies in the life course of 20–44 year old women. Special attention is paid to response and pregnancy acceptance. Exploring determinants and dynamics, this study will contribute to a better understanding of 'happiness with an unintended pregnancy', as this is assumed to be indicative of fewer social problems and health risks. Methods: Retrospective survey data on first unintended pregnancies carried to term ( n  = 2, 306) were analysed using bivariate analysis. Qualitative analysis of the narrations of such pregnancies ( n  = 59) used the technique of comparing cases. Standardised and qualitative data are available for first intended or aborted pregnancies as comparison groups. All data were collected from the cross-sectional mixed-methods study of 'Women's Lives: Family Planning in the Life Course' (2012–2018, Federal Centre of Health Education, Germany). Results: Two-fifth of the unintended pregnancies carried to term were '(very) welcome'. Pregnancy intention, contraceptive use, living conditions, and attitudes had a significant impact. Five pathways of acceptance – sooner or later, more easy or hard to achieve – were identified in the qualitative data. Conclusion: Unintended pregnancies form a continuum ranging from readily accepted 'happy' pregnancies to pregnancies hard to accept. A new measure should also include postconception acceptance, besides preconception desire.